GAMBARAN NYERI GERAK CARPAL TUNNEL SYNDROME PADA IBU RUMAH TANGGA DI DESA MADUREJO - Al Gifari, Muhammad Yusrin; Putri, Maulida Wijaya (Politeknik Unggulan Kalimantan, 2024)
Carpal Tunnel Syndrome is irritation, compression, or stretching of the median nerve when it passes through the carpal tunnel at the wrist, the symptoms of this disease are tingling and pain that radiates from the wrist to the fingers. The emergence of these symptoms causes pain when moving which interferes with daily activities in housewives. This study aims to determine the description of carpal tunnel syndrome motion pain in housewives in Madurejo Village. This research uses a type of quantitative research with a descriptive analytic research design. This study was conducted to determine the level of motion pain in housewives who have carpal tunnel syndrome using the Visual Analog Scale (VAS). Most CTS were at the age of 46-55 years (40%), activities as housewives were at most 51 (78.4%), and based on the level of motion pain the most with the interpretation of moderate pain on dorsal flexion movements were 34 people (52.4 %), and in palmar flexion movement 29 people (44.6%). Based on the results of the study, it can be concluded that the most common carpal tunnel syndrome sufferers among housewifes in Madurejo Village are aged 46-55 years, and the average experience is moderate pain.